Optimizing Pricing Strategies: Integrating Dempster-Shafer Method in Decision Support Systems for Uncertainty Management - Feriantomi, Rey; Heksana, Syaifa (International Enterprise Integration Association, 2024)
This research explores the integration of the Dempster-Shafer method within decision support systems to revolutionize pricing strategies in dynamic business environments. The study investigates the method's efficacy in managing uncertainties, synthesizing diverse evidence sources, and fostering informed decision-making in pricing scenarios. Through a structured approach, the Dempster-Shafer method enables decision-makers to navigate uncertainties, integrate multifaceted evidence, and refine pricing strategies with greater precision and adaptability. Findings showcase its transformative potential, offering insights into risk management, holistic integration of information, structured conflict resolution, and agile responsiveness to market dynamics. While demonstrating significant contributions, challenges in computational complexity, interpretability, and integration emerge, presenting avenues for further research and refinement. This research signifies a paradigm shift, emphasizing the importance of innovative computational methodologies in empowering evidence-based, proactive decision-making in pricing strategies across industries.